Effects of online reading strategy instruction on reading comprehension, strategy use and affective attributes of tertiary ESL learners - Dong, Kangxing (2023)
With the fast growth of technology and prevalent use of online reading platforms, online reading has become a main source of input for ESL learners at the tertiary level. While online reading has become ubiquitous, readers are not naturally reading online materials efficiently. One of the useful solutions to overcome the challenges for ESL learners in an online reading environment is online reading strategy instruction. It is also imperative for educators to understand clearly students’ affective attributes toward online reading as these affective attributes play an influential role in students’ reading process. This study therefore aims to investigate the effects of online reading strategy instruction on online reading comprehension performance, strategy use and affective attributes of ESL learners at the tertiary level. This study also investigates the profiles of learners’ online reading strategy use and their affective attributes toward online reading, as well as the relationships between online reading strategy use, affective attributes, and online reading comprehension. This study employed a mixed research method with pre-test post-test quasi-experimental design as the predominant data collection method. Four research instruments were used in the study, which are Second Language Online Reading Strategies Survey, Survey of Online Reading Affective Attributes, online reading test, and reflective diary. In this study, the five-stage strategy instruction model was employed to teach students reading strategies. These five stages consist of preparation stage, presentation stage, practice stage, evaluation stage, and expansion stage. There are seven types of online reading strategies instructed in this study, which include skimming, inferring, locating, translating, navigating, evaluating, and synthesizing. The affective attributes examined in this study include self-efficacy, motivation and anxiety. Results from paired samples t-tests showed that students from the experimental group improved significantly in online reading comprehension performance, strategy use and affective attributes after the strategy instruction. However, there were no significant change among students from the control group, indicating the significant effects of the five-stage strategy instruction on students’ online reading comprehension performance. Descriptive statistics showed that the students’ overall usage of online reading strategies was moderate or relatively frequent, and the students had relatively positive dispositions toward online reading. The results also revealed the significant correlations between online reading strategy use, affective attributes, and online reading comprehension at both pre- and post-instruction stages. This study contributes to the development of applied linguistics and is beneficial for students’ development of linguistic competence in L2 by examining the effects of online reading strategies. It also provides useful and specific teaching methods for educators to help students improve their use of online reading strategies. In this study, quantitative data were given priority and it is recommended for interested researchers to conduct a mainly qualitative study, and make comparison about the findings between different methodology designs. Finally, it is recommended for researchers to investigate the affective attributes individually with more focus.